Hipertensi Resisten: Diagnosis dan Tatalaksana - Rachmawan, Yogi Puji; Pratiwi, Witri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
Resistant hypertension is still one of the problems faced by clinicians in daily practice. The diagnosis of resistant hypertension requires the exclusion of pseudo-resistance. This literature review aims to determine the criteria of resistant hypertension and its management so that it can be reference of optimal management. The method used was through literature review of scientific articles published in journals, ministry of health data, and guidelines, both national and international. The literature collected was related to data on the epidemiology of hypertension, resistant hypertension, diagnosis and therapeutic management. Data searches were conducted through Google Scholar, PubMed and Scopus databases by entering keywords. Resistant hypertension is diagnosed when blood pressure has not been controlled despite receiving more than 3 types of antihypertensive drugs with one of them is diuretics or the blood pressure is only controlled after receiving ³4 types of antihypertensive drugs. Therapeutic management includes non-pharmacological, pharmacological and device intervention.